Land use activities among forest environments’ dwellers in Edo State, Nigeria: implications for livelihood and sustainable forest Management (2010)
Although urbanization may be increasing globally, over 75.0% of Nigerian populations are still living in rural areas. Extensive rainfed farming used to sustain this population is limited by loss of forest biodiversity, climate change and exposure of fragile soil. This study reports the socio-economic background of Edo State forests environments dwellers in relation to their land use activities with a view to positively harnessing the synergy of the two variables for improving human livelihood and by extension sustainable forest management. Stratified random sampling technique was used to select 296 rural dwellers in settlements within and around three forest reserves: Ehor, Okomu, and Sakpoba. Information obtained was subjected to descriptive and chi-square test statistics at p = 0.05. Results revealed that the most popular land use activity within the forest reserves is farming (94.9%). A majority of the respondents practice mixed cropping with multiple choices of major crops through the taungya5 system. Socio economic status of rural dwellers affect their awareness of forest reserves, consent to use of forest reserves, willingness to plant trees on farm land and exploitation of forest resources. While participatory management of the reserves is expected to impact the economy of the study area, awareness of and exploitation of forest reserves as well as willingness to plant trees will on the whole influence the participation of rural dwellers in the management of the reserves.